Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-10-30T14:41:43+01:00
(2x² + 3x + 1)² = (2x² - 4x - 1)²
(2x² + 3x + 1)² - (2x² - 4x - 1)² = 0
Un produit est nul si un de ses facteur est nul
2x² + 3x + 1 = 0
Δ = b² - 4ac
Δ = 3² - 4 x 2 x 1
Δ = 9 - 8
Δ = 1

Comme Δ>0 l'équation a deux solutions.

x₁ = (- 3 - 1)/(2 x 2) = - 4/4 = - 1
x₂ = (- 3 + 1)/(2 x 2) = - 2/4 = - 1/2
------------------------------------------------------
2x² - 4x - 1 = 0
Δ=  b² - 4ac
Δ = (- 4)² - 4 x 2 x (- 1)
Δ = 16 +  8
Δ = 24

x₃ = (4 - √24)/(2 x 2) = (4 - 2√6)/4 = (2 - √6)/2
x₄ = (4 + √24)/(2 x 2) = (4 + 2√6)/4 = (2 + √6)/2

\boxed{S=\{-1 \ ; \ -  \frac{1}{2} \ ; \  \frac{2-\sqrt6}{2} \ ;  \frac{2+\sqrt6}{2}  \}}